Membangun Ekonomi Negeri Ullath yang Kuat, Melalui Strategi Terpadu Dilihat Dari Ekonomi, Hukum, dan Teknik dalam Program KKN untuk Pengembangan UMKM di Provinsi Maluku - Willy Prasetyo Mainake; Kayra Faith Love Patty; Hendry Bellen; Rosalinda Huliselan; Deassy J.A Hehanussa (Yayasan Literasi Sains Indonesia, 2026)
Maluku Province is rich in natural and cultural resources with significant potential to drive local economic growth through the development of Micro, Small, and Medium Enterprises (MSMEs). Negeri Ullath boasts a strong presence in palm-based commodities, namely sopi (palm sugar palm), brown sugar, and the Tongka Langit banana. However, its economy faces various obstacles: dependence on a single product type, declining brown sugar production due to inefficient processing, seasonal banana availability, lack of business legality, low product quality, and weak management and marketing. The objective of this Community Service Program (KKN) is to build a resilient community economy through an integrated strategy that integrates economic, legal, and technical aspects. The program is implemented through educational seminars and interactive discussions, with data collection using observation and questionnaires. Evaluation results show an 84% increase in participants' understanding of business management, licensing, and product quality improvement, along with tangible improvements in the Tongka Langit banana packaging system. This approach has proven effective in reducing the knowledge gap and laying the foundation for an independent and sustainable economy based on local potential.